(3TYQ GdCRO aj GdYUQ GdLGgdj (B:s (3TYQ ef de jLeY TYQge ef TYQGA GdCRO (B/s - (3YHjO, CMeO eMeO,s 1967; - ((3CHh XHj (B:s (3gjFI CHh XHj ddSjGMI hGdKbGaI, s (3OGQ GdcJH GdhWfjI,s, 2016)
(3GHJOC gPG GdcJGH HJhKjb JGQjN GdCRO aj GdYUQ GdLGgdj; ef CfSGH bHGFd GdCRO, hCge QLGdgG, hCeGcf GfJTGQgG, hMjhGJgG GdSjGSjI hGdGbJUGOjI hGdGLJeGYjI hGdOjfjI, hPdc aj GdbSe GdChd ef GdcJGH, CeG GdbSe GdBNQ agh OjhGf GdCRO aj GdYUQ GdLGgdj, hjVe GdTYQ GdPj bGdg TYQGA GdCRO aj gPG GdYUQ eef djShG ef GdeTghQjf, hde JWHY dge OhGhjf, ZjQ Cfg de jVe TYQGA GdCRO GdcHGQ eef LeYJ OhGhjfge SGHbG Ch eef hUdJ EdjfG eNWhWGJge cMSGf Hf KGHJ GdNRQLj(B. s
(3GdeMJhjGJ (B: (3GdbSe GdChd (B: (3JGQjN GdCRO aj GdYUQ GdLGgdj, GdeHMK GdChd (B: (3fSH GdCRO hOjGQgG, GdeHMK GdKGfj (B: (3MjhGJ GdCRO, GdeHMK GdKGdK (B: (3OjhGf GdCRO(B-(3GdbSe GdKGfj (B: (3OjhGf GdCRO, CRO Gdjef, GdChS, HGQb, KGHQ, KeGdI, GdMLQ, GdMOGf, NRGYI, GdNRQL, NfjS, OhS, SdGeGf, GdYJjc, ZGeO, ZSGf, eHOYGf, GdfeQ(B...-(3TYQGA CROjhf eLghdh GdbHGFd(B-(3TYQGA CROjhf eLghdh GdCSeGA(B-(3GdagGQS GdafjI, agQS GdCHjGJ GdTYQjI(B... (3hehVhYGJ CNQi(B. s
(3HHdjhLQGajI (B: (3UaMI (B314-321.s
Keywords: (3GdCRO (B((3bHjdI(B)s -- (3TYQs; (3GdTYQ GdYQHjs -- (3JGQjN hfbOs -- (3GdYUQ GdLGgdjs; (3GdCOH GdYQHjs -- (3JGQjN hfbOs -- (3GdYUQ GdLGgdjs